Thalamus and consciousness: a systematic review on thalamic nuclei associated with consciousness - Cacciatore, Martina; Magnani, Francesca Giulia; Barbadoro, Filippo; Ippoliti, Camilla; Stanziano, Mario; Clementi, Letizia; Nigri, Anna; Nanetti, Lorenzo; Marino, Silvia; La Porta, Fabio; Lucca, Lucia Francesca; Prada, Francesco; et al. (Frontiers in Neurology, 2025)
IntroductionConsciousness relies on both cortical and subcortical structures and their feedforward and feedback pathways. Within this framework, the thalamus represents a relay station enabling the transmission, reception, and integration of information. However, it is divided into several nuclear groups each composed of functionally heterogeneous nuclei, and, to date, an agreement on which nuclei are most involved in the generation, maintenance, and modulation of consciousness is still lacking.MethodsTo fill this gap, we performed a systematic review by querying 5 electronic databases (MEDLINE/Pubmed, Scopus, EMBASE, Web of Science, and Cinahl Complete) about studies published in the last 20 years exploring the relationship between specific thalamic nuclei/nuclear groups and consciousness. For each included study, we extracted data supporting (i.e., positive evidence) or not (i.e., negative evidence) the relationship between a specific nucleus/nuclear group and the consciousness.Results167 articles were included leading to 346 pieces of evidence of which 284 were positive. Most of the retrieved positive evidence pertained to the intralaminar nuclear group, followed by the mediodorsal and ventral nuclear groups. Furthermore, when considering the specific nuclei within the intralaminar nuclear group, results highlighted the centromedian-parafascicular complex (CM-Pf) as the nucleus most related to consciousness. Despite the high heterogeneity characterizing the adopted methodologies (e.g., brain stimulation, anesthesia, brain damage), as well as the study population (e.g., either healthy and pathological humans or animals) across studies, the greatest amount of evidence supported a key role of CM-Pf for the generation, modulation, and maintenance of the level of consciousness.DiscussionThough there is more research on the role of intralaminar nuclei, there is proportionally more positive evidence supporting these nuclei (particularly the CM-Pf) as key nodes in the network underlying consciousness compared to other thalamic nuclei. These results support ongoing therapeutic approaches to disorders of consciousness by reinforcing the rationale behind brain stimulation targeting CM-Pf and paving the way for other potential candidates for targeted interventions.